A105. Evaluation of Pediatric Lung Diseases 2012
DOI: 10.1164/ajrccm-conference.2012.185.1_meetingabstracts.a2339
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Of Atopy, Airway Function, Exhaled Nitric Oxide And Cytokine Production Early In Life To Airway Function And Current Asthma At 5-Years Of Age

Abstract: Childhood asthma is characterized by atopy, airway hyper-reactivity, and airway inflammation; however, it remains unclear how Rationale these relationships develop from very early in life. We previously described that infants mean age 11 months with eczema (atopic or non-atopic) have lower forced expiratory flows, heightened airway reactivity, and elevated exhaled nitric oxide (eNO) prior to any episodes of wheezing (JACI 2008 Oct;122(4):760-5).: At 5-years of age, we have so far obtained longitudinal follow-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Finally, SB-FE NO, but not tidal-FE NO , measured prior to age 3 years was associated with BDR. Our SB-FE NO results are consistent with a recent report from a prospective cohort of infants with atopic dermatitis, but without prior wheezing wherein SB-FE NO measured at enrolment (mean age 10.7 months) was predictive of asthma as well as airway reactivity at age 5 years [33]. However, to our knowledge, our study is the first to perform SB-FE NO measurements and obtain longitudinal lung function measurements in a cohort of infants and toddlers with recurrent physician-diagnosed wheezing.…”
Section: Discussionsupporting
confidence: 92%
“…Finally, SB-FE NO, but not tidal-FE NO , measured prior to age 3 years was associated with BDR. Our SB-FE NO results are consistent with a recent report from a prospective cohort of infants with atopic dermatitis, but without prior wheezing wherein SB-FE NO measured at enrolment (mean age 10.7 months) was predictive of asthma as well as airway reactivity at age 5 years [33]. However, to our knowledge, our study is the first to perform SB-FE NO measurements and obtain longitudinal lung function measurements in a cohort of infants and toddlers with recurrent physician-diagnosed wheezing.…”
Section: Discussionsupporting
confidence: 92%
“…Chang et al reported that in their prospective cohort of infants with atopic dermatitis but without prior wheezing, SB-FE NO measured at enrollment (mean age 10.7 months) was predictive of asthma as well as airway reactivity at age 5 years. 30 However, we believe that our study is the first to perform SB-FE NO measurements in a cohort of infants and toddlers with recurrent physician-diagnosed wheezing that were then prospectively followed into the school-age years to determine the predictive value of SB-FE NO for school-age asthma, exacerbations, and lung function. Furthermore, we found that an elevated SB-FE NO (concentration ≥31.5 ppb) in wheezy infants and toddlers predicted active asthma at age 6 years with a high degree of accuracy (AUC of 0.92, sensitivity of 93%, specificity of 86%, positive predictive value of 81%, negative predictive value of 95% and a relative risk of 16).…”
Section: Discussionmentioning
confidence: 99%